Efficacy of TachoSil® in preventing hemorrhage after loop electrosurgical excision procedure. (November 2015) - Kim, Jeong Jin; Kim, Woo Young; Lee, Doo Haeng; Kang, Jun Hyeok; Song, Taejong; Lee, Kyo Won; Kim, Kye Hyun
Abstract: Study objective: To assess the utility of TachoSil for achieving hemostasis after loop electrosurgical excision procedure (LEEP). Design: Case–control study (Canadian Task Force Classification II-2). Setting: University hospital. Patients: One hundred seventy-three patients who underwent LEEP. Interventions: Patients were managed by LEEP with application of TachoSil (TachoSil group, n  = 75) or without application of TachoSil (control group, n  = 94). Measurements and main results: Patient characteristics (age, specimen depth, resection margin, LEEP histopathology, or use of TachoSil) except for parity were similar between the two study groups. Severe bleeding requiring any intervention developed in 14% of patients (24 of 169 patients), without any statistically significant difference between the two groups (11% in the TachoSil group vs. 17% in the control group; P  = 0.274). On the logistic regression analysis, other potential clinico-pathologic parameters, including age, parity, specimen depth, involvement of the resection margin, and LEEP histopathology, were not correlated with severe bleeding after LEEP. Conclusion: The use of TachoSil may not reduce the incidence of severe bleeding after LEEP.